Prevalence of opioid dependence in Scotland 2015–2020: A multi‐parameter estimation of prevalence (MPEP) study. - Markoulidakis, Andreas; Hickman, Matthew; McAuley, Andrew; Barnsdale, Lee R.; Welton, Nicky J.; Glancy, Megan; Shivaji, Tara; Collins, Craig; Lang, Jaroslaw; de Wit, Femke; Hunt, Gordon; Wilkinson, Levin; et al. (Addiction)
Background and aims: Drug‐related deaths in Scotland more than doubled between 2011 and 2020. To inform policymakers and understand drivers of this increase, we estimated the number of people with opioid dependence aged 15–64 from 2014/15 to 2019/20. Design: We fitted a Bayesian multi‐parameter estimation of prevalence (MPEP) model, using adverse event rates to estimate prevalence of opioid dependence jointly from Opioid Agonist Therapy (OAT), opioid‐related mortality and hospital admissions data. Estimates are stratified by age group, sex and year. Setting: Scotland, 2014/15 to 2019/20. Participants: People with opioid dependence and potential to benefit from OAT, whether ever treated or not. Using data from the Scottish Public Health Drug Linkage Programme, we identified a baseline cohort of individuals who had received OAT within the last 5 years, and all opioid‐related deaths and hospital admissions (whether among or outside of this cohort). Measurements Rates of each adverse event type and (unobserved) prevalence were jointly modelled. Findings The estimated number and prevalence of people with opioid dependence in Scotland in 2019/20 was 47 100 (95% Credible Interval [CrI] 45 700 to 48 600) and 1.32% (95% CrI 1.28% to 1.37%). Of these, 61% received OAT during 2019/20. Prevalence in Greater Glasgow and Clyde was estimated as 1.77% (95% CrI 1.69% to 1.85%). There was weak evidence that overall prevalence fell slightly from 2014/15 (change −0.07%, 95% CrI ‐0.14% to 0.00%). The population of people with opioid dependence is ageing, with the estimated number of people aged 15–34 reducing by 5100 (95% CrI 3800 to 6400) and number aged 50–64 increasing by 2800 (95% CrI 2100 to 3500) between 2014/15 and 2019/20. Conclusions: The prevalence of opioid dependence in Scotland remained high but was relatively stable, with only weak evidence of a small reduction, between 2014/15 and 2019/20. Increased numbers of opioid‐related deaths can be attributed to increased risk among people with opioid dependence, rather than increasing prevalence.